Effect of zinc sources and levels on sunflower (Helianthus annuus L.) hybrid in Alfisol: EFFECT OF ZINC SOURCES AND LEVELS ON SUNFLOWER HYBRID IN ALFISOL - SAMEENA KHATHOON,; T ANJAIAH,; I Y L N MURTHY,; T PRABHAKAR REDDY,; CH ARUNA KUMARI, (Journal of Oilseeds Research, 2015)
A field experiment was conducted at Indian Institute of Oilseeds Research during the rainy season of 2014 with sunflower (Helianthus annuus L.) hybrid DRSH-1 as a test crop on Alfisol. Three different zinc sources (ZnSO4 .7H2O, ZnSO4 .H2O and Zn-EDTA) and levels (10, 15 and 20 kg/ha) with recommended dose of N, P2O5 and K2O @ 90, 60 and 30 kg/ha were applied to soil to study the plant parameters i.e., plant height, stem girth, head diameter at 90 days after sowing. Seed yield was recorded at harvest. Plant height, stem girth and head diameter increased up to 20 kg Zn/ha application. Highest plant height (170.3 cm) and greater head diameter (17.6 cm) and highest stem girth (8.1 cm) and seed yield (1680 kg/ha) were achieved with the application of 20 kg ZnSO4 .H2O/ha.